The Comparison Of Service Quality For Bpjs And Non Bpjs Users In Batam Health Facilities - Rini Susanti; Victor E. D Palapessy (International Journal of Science, Technology & Management, 2021)
BPJS and Non BPJS dependent patients have the same rights as other general patients to receive satisfying services just like other health care facilities. Considering that, this new program from the government in the health sector is aimed at controlling the quality and costs of health, so that it can be accessed by all levels of society, as well as having good prospects for hospitals and other health care facilities. Thus, hospitals are responsible for being able to provide satisfying and quality services so that they can be chosen by the community, both BPJS and non BPJS participants. The purpose of this study was to compare the quality of BPJS and Non BPJS dependent health services on the satisfaction of inpatients in health care facilities in the Riau Archipelago. This type of research is quantitative using a cross-sectional approach. The sample in this study was 60 people. The instrument used is a questionnaire. Data analysis in this study used the independent t-test. The results of the study found that there were significant differences between the quality of health services for the BPJS and Non BPJS respondent groups. And there is a significant difference between the satisfaction of inpatients in the BPJS and Non BPJS respondent groups. It is hoped that this research can be a reference for future research.